Kinerja Penyuluh Pertanian dan Produktivitas Padi Sawah di Kecamatan Poleang Utara Kabupaten Bombana - Nurhalima Nurhalima; Dasmin Sidu; Salahuddin Salahuddin (Fakultas Pertanian Universitas Halu Oleo, 2021)
This study aimed to: (1) Determine the performance of agricultural instructors in lowland rice, (2) Determine the productivity of lowland rice, (3) Determine the relationship between the performance of agricultural instructors and productivity of lowland rice. This research was conducted in Poleang Utara District, Bombana Regency, which was carried out from January to February 2021 with 61 respondents who were determined by proportional random sampling, the data were analyzed descriptively and correlation analysis of Spearman rank. The research data showed that (1) The performance of agricultural extension workers in North Poleang District, Bombana Regency still needs to be improved, especially at the implementation and evaluation stages of agricultural extension. (2) The productivity of lowland rice in North Poleang District is 4.29 tons/ha. This productivity is still below the productivity of lowland rice at the level of Southeast Sulawesi Province, which is 6 tons/ha (3) The relationship between the performance of agricultural extension workers and lowland rice productivity in North Poleang District, Bombana Regency showed a strong relationship, meaning that the performance of agricultural extension workers and lowland rice productivity It is obtained those farmers support each other.